Adhesion of bacterial on metal surfaces : effect of surface roughness - Noratiqah, Chik (2015)
This research reviews the adhesion of bacterial on metal surfaces and the effect of metal’s surface roughness to the bacterial adhesion. The objectives of this research are, to study the adhesion of bacterial on metal surfaces (Stainless Steel (N690), Stainless Steel (AV220SC) and Titanium) used in medical application and the effect of surface roughness on the wettability thus adhesion. Three types of bacteria were used for this research which was Escherichia coli, Bacillus subtilis, and Staphylococcus aureus attached on the individual metal which has eight different ranges of surface roughness, achieved by fabricating using electro depositing machine (E) and electropolishing (P) techniques. The adhesion test was done for 4 hours for each bacterium with different types of metal and surface roughness. After the adhesion test, the attached bacteria on metal surfaces were dyed using fluorescence dye, SYTO9 and examined under the fluorescence microscope. The number of attached cells was counted and results were displayed as number attached per square area. Besides that, the absorbance and the colony forming unit (CFU) were also measured and the surface which gives highest optical density (OD) was identified. Finally, metal with highest attachment of bacterial, were analyzed under Scanning Electron Microscopy (SEM) to observe the bacterial cells attachments. Results obtained indicated that E. coli was a Gram negative bacterium while both B. subtilis and S. aureus were Gram positive bacteria. After the adhesion test, the OD reading for E. coli shows the highest reduction which is in the range of 6% to 45.7% compared to others bacterial solution. CFU plating for E. coli at dilution factor 102 also showed the lowest among others after the adhesion test. Besides that, the adhesion of bacterial on Stainless Steel (N690) recorded that, the highest attachment of all bacterial were on smooth surface (Ra = 0.163 μm) and rough surface (Ra = 2.910) with the total adhesion were 0.1833/ μm2 and 0.1755/ μm2 respectively. Meanwhile, adhesion on Stainless Steel (AV220SC) and Titanium shows similar trend where both B. subtilis and S. aureus provide the highest adhesion at the roughness 0.110 μm and 0.104 (smooth surface), respectively. On the other hand, the adhesion of bacterial on different metal with the same roughness (Ra = ~0.15 μm) showed that B. subtilis like to adhere to Titanium surface with the adhesion value 0.9601/μm2, while S. aureus and E. coli were adhered at Stainless Steel (N690) and Stainless Steel (AV220SC), respectively with the total adhesion 0.0679/μm2 and 0.0704/μm2 each.